Actinodaphne notabilis, Berberis yingii, Diospyros communis, Rosa miopannonica, and Symplocos ecuadorica, new replacement names for the homonyms of fossils - Doweld, Alexander B. (Phytotaxa, 2017)
Five new names are proposed for taxa that were revealed to be later homonyms in course of generating the International Fossil Plant Names Index (IFPNI): Actinodaphne notabilis for A. cuspidata Gamble (extant) non A. cuspidata Friedrich (fossil), Diospyros communis for D. dubia Göppert (fossil) non D. dubia Wallich ex De Candolle (extant), Berberis yingii for B. longispina Ying (extant) non B. longispina Miki (fossil), Rosa miopannonica for R. styriaca Kovar-Eder & Krainer (fossil) non R. styriaca Sabransky (extant) and Symplocos ecuadorica for S. globosa Ståhl (extant) non S. globosa Ludwig (fossil). The name A. cuspidata Gamble is lectotypified.